Tofacitinib is a modern solution to the problem of resistant rheumatoid arthritis - I. V. Menshikova; V. V. Strogonova (Современная ревматология, 2019)
Objective: to analyze the efficacy of tofacitinib (TOFA) in patients with an advanced stage of rheumatoid arthritis (RA) and previous methotrexate (MTX) failure according to comprehensive clinical and laboratory examination.Patients and methods. Nineteen patients (11 women and 8 men aged 29 to 71 years (mean age 53.47±10.53 years)) with a reliable diagnosis of RA according to the 2012 American College of Rheumatology (ACR) criteria were followed up. Due to a high disease activity (DAS28 averaged 5.84±0.89), the patients were prescribed TOFA 10 mg/day taken for 12 months. The disease activity indicators were assessed at baseline, 3, 6, and 12 months after the start of the study.Results and discussion. The effect of TOFA developed quite quickly: at 3 months of therapy, there were positive clinical, laboratory, and instrumental changes in most patients; 5 (26.3%) patients achieved the goal of treatment. At 12 months of therapy, 8 patients achieved DAS28 remission and 3 patients had a low disease activity; moderate RA activity persisted in 7 patients; and a high disease activity was seen in 1 patient; these SDAI activity indicators were observed in 2, 8, 7, and 2 patients, respectively. According to the ACR criteria, 20, 50, and 70% improvements were achieved by 8, 6, and 3 patients, respectively. No serious adverse reactions were recorded. The findings confirm the good efficacy and safety of TOFA in the treatment of patients with an advanced stage of RA.Conclusion. The innovative mechanism of TOFA allows a significant number of patients, in whom MTX therapy was not effective enough, to achieve the goal of treatment.